Association between red cell distribution width-to-albumin ratio and all-cause mortality in critically ill cirrhotic patients with sepsis: a retrospective analysis of the MIMIC-IV database - Jinfeng Li; Shifeng Pang; Huiya Huang; Yangni Lu; Tingting Tang; Jianlin Wu; Maowei Chen (Frontiers in Medicine)
BackgroundCritically ill cirrhotic patients are at high risk of infections, which are associated with significantly increased mortality. The red cell distribution width-to-albumin ratio (RAR) is a validated predictor of mortality in critically ill patients. However, the prognostic value of RAR in critically ill cirrhotic patients with sepsis has not been fully established.MethodsThis study retrospectively analyzed data from the Medical Information Mart for Intensive Care (MIMIC-IV) database. Patients were stratified into quartiles based on RAR values. The primary outcomes were 30-day and 365-day all-cause mortality. Kaplan–Meier survival analysis and multivariable Cox regression models were applied to assess the association between RAR and mortality. Restricted cubic spline (RCS) analysis confirmed a linear relationship and subgroup analyses explored potential interactions.ResultsA total of 2,100 patients were included. Elevated RAR values were significantly associated with increased 30-day and 365-day all-cause mortality. Compared with the lowest quartile, patients in the highest RAR quartile had a 51% higher risk of 30-day mortality [hazard ratio (HR) = 1.51, 95% confidence interval (CI): 1.19–1.92) and a 51% higher risk of 365-day mortality (HR = 1.51, 95% CI: 1.25–1.81). RCS analysis confirmed a significant linear relationship between RAR and mortality risk. Subgroup analyses showed a stronger association between RAR and mortality in elderly patients.ConclusionIn critically ill cirrhotic patients with sepsis, elevated RAR values are independently associated with increased all-cause mortality risk. This study highlights the potential of RAR as a prognostic biomarker, particularly in elderly patients.